Codiffusion of technologies in social networks - Lazzati, Natalia (American Economic Journal: Microeconomics)
This paper studies the diffusion process of two complementary technologies among people who are connected through a social network. It characterizes adoption rates over time for different initial allocations and network structures. In doing so, we provide some microfoundations for the stochastic formation of consideration sets. We are particularly interested in the following question: suppose we want to maximize technology diffusion and have a limited number of units of each of the two technologies to initially distribute$1 (Bhow should we allocate these units among people in the social network?s
Keywords: Economic Anthropology; Language; Social and Economic Stratification, Technological Change: Choices and Consequences; Diffusion ProcessesInformation and Knowledge; Communication; Belief; Unawareness